Editorial - Jože Kropivšek (Les, 2020)
The year 2020, which is slowly coming to an end, was special in several respects. First and foremost, it was marked by the Covid-19 pandemic, which severely limited physical contact and, more importantly, completely changed our work and business habits. Literally overnight, we were forced to switch to (almost) entirely digital communications and telecommuting. As it turned out, we were obviously working in the right direction in the past, because this transition did not stop us completely. We also proved our digital competence in the editorial board of Les/Wood and continued our work smoothly, and already in late spring, when the first wave of the epidemic was just ending, published the spring issue, as planned for that time. It was a similar story for this issue. All the editorial meetings, the work on common documents, all the communication with authors and reviewers went online without major issues. Many thanks to all those involved in this process for their willingness to take on new challenges.